Comprehensive Review of Pharmaceutical Advancements, Patient Care Models, and Drug Safety - Alhawiti, Sari Mohammed; Alatawi, Abdullah Salman; Alsharari, Naif Shayish; Albalawi, Hamad Saad; Alsharqawi, Ziyad Saleh S; Albaqami, Amal Aydh; Albalawi, Abdulaziz Saleh; Alfaqeih, Ahmed Abdulrahman; Albalawi, Hani Saeed Hamoud; Alenezi, Adnan Aed Baraka (Journal of Ecohumanism, 2024)
This review disseminates new developments in this industry, changes in the care delivery systems, and innovations in drug safety. Pharmaceuticals have brought innovative changes within their field of drug formation, new theories regarding medicine for individuals, and introducing biotechnologies. At the same time, patient care models are changing towards the more integrated and patient-oriented ones. Further, maintaining drug safety continues to be a critical focal point because the complexity of drug therapies continues to increase, and their potential adverse effects need to be minimized. This review, therefore, looks at these interconnections based on current literature, research findings, and case studies in a bid to give an overall vision of the evolution of modern pharmaceuticals and how their advancement impacts the delivery of healthcare.